Silicon: a duo synergy for regulating crop growth and hormonal signaling under abiotic stress conditions. (1st November 2016) - Kim, Yoon-Ha; Khan, Abdul Latif; Lee, In-Jung
Abstract: Abiotic stresses, such as salinity, heavy metals and drought, are some of the most devastating factors hindering sustainable crop production today. Plants use their own defensive strategies to cope with the adverse effects of these stresses, via the regulation of the expression of essential phytohormones, such as gibberellins (GA), salicylic acid (SA), jasmonates (JA), abscisic acid (ABA) and ethylene (ET). However, the efficacy of the endogenous defensive arsenals of plants often falls short if the stress persists over an extended period. Various strategies are developed to improve stress tolerance in plants. For example, silicon (Si) is widely considered to possess significant potential as a substance which ameliorate the negative effects of abiotic stresses, and improves plant growth and biomass accumulation. This review aims to explain how Si application influences the signaling of the endogenous hormones GA, SA, ABA, JA and ET during salinity, wounding, drought and metal stresses in crop plants. Phytohormonal cross talk plays an important role in the regulation of induced defences against stress. However, detailed molecular and proteomic research into these interactions is needed in order to identify the underlying mechanisms of stress tolerance that is imparted by Si application and uptake.